Medical Waste Management in Community Health Centers - Jafar Sadegh TABRIZI; Ramin REZAPOUR; Mohammad SAADATI; Samira SEIFI; Behnam AMINI; Farahnaz VARMAZYAR (Tehran University of Medical Sciences, 2018)
Background: Non-standard management of medical waste leads to irreparable side effects. This issue is of double importance in health care centers in a city which are the most extensive system for providing Primary Health Care (PHC) across Iran cities. This study investigated the medical waste management standards observation in Tabriz community health care centers, northwestern Iran. Methods: In this triangulated cross-sectional study (qualitative-quantitative), data collecting tool was a valid checklist of waste management process developed based on Iranian medical waste management standards. The data were collected in 2015 through process observation and interviews with the health center's staff. Results: The average rate of waste management standards observance in Tabriz community health centers, Tabriz, Iran was 29.8%. This case was 22.8% in dimension of management and training, 27.3% in separating and collecting, 31.2% in transport and temporary storage, and 42.9% in sterilization and disposal. Lack of principal separation of wastes, inappropriate collecting and disposal cycle of waste and disregarding safety tips (fertilizer device performance monitoring, microbial cultures and so on) were among the observed defects in health care centers supported by quantitative data. Conclusion: Medical waste management was not in a desirable situation in Tabriz community health centers. The expansion of community health centers in different regions and non-observance of standards could predispose to incidence the risks resulted from medical wastes. So it is necessary to adopt appropriate policies to promote waste management situation.